Efektivitas Pembelajaran Daring melalui Zoom Cloud Meetings pada Mata Pelajaran Kearsipan di SMK Ketintang Surabaya - Nadiyah Rodlotul Jannah; Durinda Puspasari (Edunusa: Journal of Economics and Business Education, 2022)
The purpose of this study is to analyze the effectiveness of learning online through zoom cloud meetings on the subjects of archives in SMK Ketintang Surabaya. This research is a descriptive research with a qualitative approach. Data collection techniques are interviews and questionnaires. The validity of data using triangulation of sources. The technique of data analysis using the Model of Miles and Huberman, namely data collection, data reduction, data presentation, and conclusion. The results showed that learning online through zoom cloud meetings on the subjects archival grade X OTKP 2 SMK Ketintang Surabaya has been running effective based on 4 indicators of the effectiveness of learning: in terms of the quality of learning, it can be seen from the process and results in learning in class X OTKP 2 SMK Ketintang Surabaya using learning media zoom cloud meetings that is quite accessible and easy to use. Learning outcomes students who meet the standard value of the Minimum Completeness Criteria (KKM) is 90% of students; in terms of the suitability of the level of learning, can be seen from the readiness of teachers and students on learning such as the fulfillment of the facilities and infrastructure that HP or laptop, wireless or internet quota, the teacher gives the material to be studied in advance by the students; in terms of incentives, it can be seen from the activity of the teacher in giving motivation to the students of class X OTKP 2 SMK Ketintang Surabaya each will begin the lesson by providing stimulus through a positive story and give advice. Teachers also provide additional value or points to students who are active; in terms of time, it can be seen from the teachers who give a deadline for a task, Students can complete the task on time in accordance with the time specified by the teacher